The effect of body composition on pulmonary function in elite athletes - Kocahan, Tuğba; Akınoğlu, Bihter (Progress in Nutrition, 2019)
The pulmonary function is one of the most basic factors that determine athletic performance. The purpose of this study was to investigate the correlation of the body weight, body fat percentage (fat%), body fat mass, fat-free mass, muscle mass, abdominal muscle mass, and waist and hip circumference on the forced expiratory volume curve and maximal voluntary ventilation. A total of 398 elite athletes composed of 254 male and 144 female (mean age, 16.63±2.28 years) were enrolled for this study. The study involved the measurements of the body composition by bioelectrical impedance method, and forced vital capacity (FVC); forced expiratory volume at 1 second (FEV1); forced expiratory flow during the middle half of the FVC (FEF25-75) from the forced expiratory volume curve; and maximal voluntary ventilation (MVV) by spirometry. Correlation and multiple regression analysis between the body composition and pulmonary function were used. It was determined that there was an important relationship between the demographic characteristics and body composition parameters of the athletes and the pulmonary function test values. This relationship was categorized as low, medium, high and very high (p <0.05). During the multiple regression analysis related to the body composition of the entire group, it was determined that the statistically significant predictors of FVC were age, body weight, height, hip circumference and body fat percentage (R=.883, R²=.780, Adj R²=.777) (p<0.05). Statistically significant predictors of FEV1 were age, body weight, height, hip circumference and body fat percentage (R=.872, R²= .761, Adj R²=.758) (p<0.05). Statistically significant predictors of FEF25-75 were age, body weight, height, body fat percentage and muscle mass (R= .728, R²= .530, Adj R²=.524) (p<0.05). Finally, significant predictors of MVV were age, body weight, height, waist circumference, hip circumference and body fat percentage (R= .774, R²= .599, Adj R²= .591) (p<0.05). At the end of our study, we have determined that the factors affecting the pulmonary function in both male and female athletes were not limited to age, gender, and body weight, but also included the body composition parameters such as the body fat percentage, body fat mass, muscle mass, fat-free body mass, trunk muscle mass, trunk fat mass, and waist and hip circumference.